2017
DOI: 10.1149/2.0391713jes
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Electrochemical Study of Welded Al Alloys Joined by Friction Stir Welding

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible. This is an author-deposited version published in : http://oatao.univ-toulouse.fr/ Eprints ID : 19842To link to this article :

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 53 publications
1
9
0
1
Order By: Relevance
“…The development of techniques for in situ characterization of localized electrochemical activities has helped to add more insight into the understanding of SLC initiation and propagation. A few studies have successfully employed techniques such as scanning electrochemical microscopy (SECM) [16], scanning vibrating electrode technique (SVET) [17][18][19] and localized electrochemical impedance spectroscopy (LEIS) [20] to reveal the corrosion modes and the regions that are most susceptible to corrosion in friction stir weldments. Thus, in this work, localized electrochemical techniques including the SVET and LEIS have been employed to reveal the difference between the corrosion behaviour of the advancing and retreating sides of the friction stir weldment of the AA2024-T3 alloy.…”
Section: Introductionmentioning
confidence: 99%
“…The development of techniques for in situ characterization of localized electrochemical activities has helped to add more insight into the understanding of SLC initiation and propagation. A few studies have successfully employed techniques such as scanning electrochemical microscopy (SECM) [16], scanning vibrating electrode technique (SVET) [17][18][19] and localized electrochemical impedance spectroscopy (LEIS) [20] to reveal the corrosion modes and the regions that are most susceptible to corrosion in friction stir weldments. Thus, in this work, localized electrochemical techniques including the SVET and LEIS have been employed to reveal the difference between the corrosion behaviour of the advancing and retreating sides of the friction stir weldment of the AA2024-T3 alloy.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a localized pH decrease occurred over the HAZ regions, as indicated by the red color scales, which was more intense on the localized corrosion sites. These sites are associated with the occurrence of SLC, and strong anodic activity is observed at these locations when coupled to the WJ, as shown in Figures 6(a Although galvanic coupling effects in other FSW Al-alloys have been characterized using the agar gel test [9,19,34], some controversy exists in the literature about the applicability of this test due to the hindrance to the free circulation of ions in the gel environment. In order to further investigate the cathodic and anodic regions on these welded zones from the associated pH changes in the adjacent electrolyte, localized microelectrochemical techniques would be advisable and they were employed in our work as described below.…”
Section: Visualization Of Corrosion Activitymentioning
confidence: 99%
“…In addition, few attempts have been made to investigate these localized processes using localized electrochemical techniques [19,31], although the applicability of localized electrochemical techniques for the investigation of the corrosion activity of some Al-Cu-Li alloys has been reported in the literature [7,29,30,32]. Thus, scanning probe techniques with electrochemical selectivity, such as the scanning vibrating electrode technique (SVET), scanning electrochemical microscopy (SECM) and the local electrochemical impedance spectroscopy (LEIS), were employed to study galvanic coupling effects on the local electrochemical activity due to the different zones in contact in dissimilar Al-alloys welded by FSW, namely for the 7050/2024 [33], 2024/7475 [34], and 2050/7449 systems [35]. In those works, these localized electrochemical techniques were shown useful to evaluate the local electrochemical response in the different zones resulting from FSW of different Alalloys.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the authors also found that the IGC attack was observed in all the weld zones with severe effect in HAZ of AA2024-T3 owing to high corrosion susceptibility and heterogeneous distribution of precipitates in AA2024-T3 as compared to AA7050-T7611. de Abreu et al 129 reported the corrosion behaviour of FSWed AA2024-T3 and AA7475-T761 joints by exposing the weld samples to 0.1 molL �1 Na 2 SO4 þ 0.001 mol L �1 NaCl solutions. It was observed that corrosion attack of joints was established from the galvanic coupling in which the AA7475-T761 shows anodic nature with respect to AA2024-T3.…”
Section: Effect Of Peak Ageing Ageing Increases Corrosion Resistance Of Fswed Jointsmentioning
confidence: 99%